PYK2 selectively mediates signals for growth versus differentiation in response to stretch of spontaneously active vascular smooth muscle. Issue 7 (17th July 2014) - Bhattachariya, Anirban; Turczyńska, Karolina M.; Grossi, Mario; Nordström, Ina; Buckbinder, Leonard; Albinsson, Sebastian; Hellstrand, Per
Abstract Stretch of vascular smooth muscle stimulates growth and proliferation as well as contraction and expression of contractile/cytoskeletal proteins, all of which are also regulated by calcium‐dependent signals. We studied the role of the calcium‐ and integrin‐activated proline‐rich tyrosine kinase 2 (PYK2) in stretch‐induced responses of the rat portal vein loaded by a hanging weight ex vivo. PYK2 phosphorylation at Tyr‐402 was increased both by a 10‐min stretch and by organ culture with load over several days. Protein and DNA synthesis were reduced by the novel PYK2 inhibitor PF‐4594755 (0.5–1 μmol/L), while still sensitive to stretch. In 3‐day organ culture, PF‐4594755 caused maintained myogenic spontaneous activity but did not affect contraction in response to high‐K+ (60 mmol/L) or to α1‐adrenergic stimulation by cirazoline. Basal and stretch‐induced PYK2 phosphorylation in culture were inhibited by PF‐4594755, closely mimicking inhibition of non‐voltage‐dependent calcium influx by 2‐APB (30 μmol/L). In contrast, the L‐type calcium channel blocker, nifedipine (1 μmol/L) eliminated stretch‐induced but not basal PYK2 phosphorylation. Stretch‐induced Akt and ERK1/2 phosphorylation was eliminated by PF‐4594755. PYK2 inhibition had no effect on mRNA expression of several smooth muscle markers, and stretch‐sensitive SM22α synthesis was preserved. Culture of portal vein with the Ang II inhibitor losartan (1 μmol/L) eliminated stretch sensitivity of PYK2 and Akt phosphorylation, but did not affect mRNA expression of smooth muscle markers. The results suggest that PYK2 signaling functionally distinguishes effects of voltage‐ and non‐voltage‐dependent calcium influx. A small‐molecule inhibitor of PYK2 reduces growth and DNA synthesis but does not affect contractile differentiation of vascular smooth muscle.